2020
DOI: 10.1039/d0sc02777d
|View full text |Cite
|
Sign up to set email alerts
|

Aryl urea substituted fatty acids: a new class of protonophoric mitochondrial uncoupler that utilises a synthetic anion transporter

Abstract: A new mitochondrial uncoupler that forms membrane permeable dimers through interactions of remote acidic and anion receptor groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…To quantitatively characterize the efficiency of these compounds to modulate cellular pH, we carried out concentration-dependent experiments and determined the EC 50 values that are dened as the concentrations required to shi the orange/green ratios of AO by 50%. 43 The EC 50 values were listed in Table 2, and show that compounds 1-12 alkalize acidic organelles in the order of compound 12 > 11 > 8 > 10 > 9 > 7 > 6 > 5 > 1 z 2 z 3 z 4, which is consistent with their transport activity on vesicles.…”
Section: Lysosomal Ph-modulating Effectmentioning
confidence: 63%
“…To quantitatively characterize the efficiency of these compounds to modulate cellular pH, we carried out concentration-dependent experiments and determined the EC 50 values that are dened as the concentrations required to shi the orange/green ratios of AO by 50%. 43 The EC 50 values were listed in Table 2, and show that compounds 1-12 alkalize acidic organelles in the order of compound 12 > 11 > 8 > 10 > 9 > 7 > 6 > 5 > 1 z 2 z 3 z 4, which is consistent with their transport activity on vesicles.…”
Section: Lysosomal Ph-modulating Effectmentioning
confidence: 63%
“…The kinetics of HCA + HOOc reactions in water were estimated using the competing FHT and SET processes, as in prior research. 55,65,67,72 Eqn (7) was used to obtain the rate constants of the states (k state ), while eqn ( 8)- (10) were used to calculate the rate constant incorporating the molar fraction (k f ), the total rate constant (k total ) and the overall rate constant (k overall ) that included the f value of HOOc (pK a (HOOc) ¼ 4.8). 73 Table S2, ESI, † and Table 4 describe the ndings, whereas Fig.…”
Section: 2mentioning
confidence: 99%
“…4 HCA has attracted much attention because they are the most important antioxidants in our diet. [5][6][7][8][9][10] Nenadis et al reported HCA i.e. 3, 4 and 5 exhibited a good radical scavenging activity via the 2,2-diphenyl-1-picrylhydrazyl (DPPHc) and 2,2 0 -azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTSc + ) assays.…”
Section: Introductionmentioning
confidence: 99%
“…Last year, Rawling et al reported a series of fatty acid substituted urea-based (also termed as, aryl-urea) anion transporters (45 a-45 d) and their function as mitochondrial uncouplers. [48] The carboxylic acid group and a π-conjugated motif were separated by a long alkyl chain and the aryl-urea group engaged in forming intermolecular H-bonds with the fatty acid carboxylate, facilitating permeation across mitochondrial inner membrane (MIM) alongside repetitive cycling. These compounds induced mitochondrial dysfunction in breast cancer cells and damaged ATP production at concentrations exceeding their JC-1 IC 50 (at 10 and 40 μM).…”
Section: Acyclic Anionophores Based On Urea and Thioureamentioning
confidence: 99%